Emotional Intelligence as a Predictor of Research Skills Acquisition Among University Students with Intellectual Disabilities in Calabar, Nigeria - Nwogwugwu, Chidirim Esther; Uchegbue, Henrietta Osayi; Ovat, Sylvia Victor; Uka, Nnenna Kalu; Egbai, Julius Michael; Chilebe Iwuala, Patricia Ebere; Effiom, Anthony Pius; Andong, Helen Akpama; Ojini, Richard Ayah; Igajah, Mayen Ndaro; Umoh, Margaret Sylvanus; Omoogun, Remi Modupe; et al. (Journal of Intellectual Disability - Diagnosis and Treatment, 2025)
Aim: Intellectual disability is characterized by significant limitations in intellectual functioning and adaptive behavior originating before age 18 (AAIDD, 2010). In higher education, these students often require individualized support, yet inclusive practices in Nigerian universities remain underdeveloped. This study examines the predictive relationship between emotional intelligence and research skills acquisition among university students with intellectual disabilities at the University of Calabar (UNI.CAL) and the University of Cross River (UNICROSS), Cross River State, Nigeria. Five study objectives were stated to guide the research. Five research questions were formulated, and three hypotheses were stated. Literature was reviewed based on the variables under study, as research gaps were also stated. Method: The study adopted a correlational survey research design. The area of the study is Cross River State, South-South, Nigeria. The study population consists of all 20,030 final-year undergraduate students with intellectual disabilities in inclusive departments of the University of Calabar and the University of Cross River State, offering special education or support for students with disabilities. A purposive sampling technique was used to select students identified with intellectual disabilities. A sample size of 401 participants was selected based on accessibility and consent. The instrument for data collection was a questionnaire. Cronbach Alpha reliability coefficient method was used in establishing the reliability index of .82. Results of the research questions were presented using frequency counts, percentages, mean and standard deviation, and Pearson's Product Moment Correlation, Multiple linear regression, and Independent t-test were used to analyze the research question and hypotheses. Results: The results revealed that emotional intelligence significantly contributes to developing research skills in students with intellectual disabilities. Emotional competencies such as self-awareness, motivation, and interpersonal sensitivity are essential tools in enabling these students to participate fully in research activities. Hence, emotional intelligence components collectively predict research skills acquisition. There is a significant difference between male and female students with intellectual disabilities in their level of research skills acquisition. Conclusion: This research concluded that there is a statistically significant relationship between emotional intelligence and the ability to develop and perform research tasks. It affirms the critical role emotional intelligence plays not just in social functioning but also in academic productivity, especially among students who often face exclusion or limited support. Recommendation: Universities should incorporate emotional intelligence training into their special education and general academic programs to build students’ self-efficacy and research competence.